Eksplorasi Desain Dasar (Nirmana) melalui Kombinasi Media Grafis Analog dan Digital: Suatu Penelitian Kelas/Studio - Anita Rahardja; Dyah Gayatri Puspitasari; Monica Wiguna (Bina Nusantara University, 2013)
This article is based on a research aiming to contextualize the fundamental principles of art and design to current setting in which analog media are no longer chosen as the ultimate hardware/tools. It is important considering digital hardware becomes more and more prevalent even preferred by students, whereas analog tools are getting harder to obtain, expensive and less ecological friendly. The goal of this research is to produce method analysis and the creation of two-dimensional basic design through digital media (Camera) followed by conventional drawing tools, documented and conducted by the lecturers and the students. So far, almost 100% of the studies concerning basic design could only be found in foreign publications, with visual work examples that cannot be used freely in Indonesian local education due to copyright issue. Therefore, a literature study is conducted to examine the formal objects of this research which are the elements and fundamental principles in design, followed by ideation and visualization processes carried by the students in basic design classes through the semester. The visualization itself will integrate analog and digital media to generate the material objects of the research, which is a series of two dimensional design compositions. These compositions are then analyzed and classified to taxonomic category of fundamental principles of two-dimensional design as an integral part of teaching-learning process (self-evaluation class for future improvement).